2015
DOI: 10.1167/iovs.14-16080
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Systemic Hypertension and Macular Thickness Measured by Optical Coherence Tomography

Abstract: Systemic hypertension was inversely associated with macular thickness in most macular subfields, particularly in subjects with an elevated fasting glucose level. This finding suggests that it may be necessary to consider the presence of hypertension when macular thickness and pericentral macular area volume are evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 32 publications
3
28
1
Order By: Relevance
“…More studies need to be done to establish the effect of retinal microvascular changes seen in hypertensive eyes and its impact on the outer retina, photoreceptors and ultimately visual function. Similar to a previous study by Kong et al on OCT findings in hypertensive eyes, a decrease in peri-foveal macular thickness was observed in the univariate analysis however this was no longer significant in the between the hypertensive and control groups in our multivariate analysis 56 . In contrast to another cross-sectional cohort study by Lee et al which found a reduction in the foveal vessel density, perfusion density, mean GC-IPL thickness, CFT and RNFL and an increase in the FAZ at the level of the SVP in the hypertensive group compared to controls, our paper did not find any significant differences between the 2 groups at the level of the SVP.…”
Section: Discussionsupporting
confidence: 90%
“…More studies need to be done to establish the effect of retinal microvascular changes seen in hypertensive eyes and its impact on the outer retina, photoreceptors and ultimately visual function. Similar to a previous study by Kong et al on OCT findings in hypertensive eyes, a decrease in peri-foveal macular thickness was observed in the univariate analysis however this was no longer significant in the between the hypertensive and control groups in our multivariate analysis 56 . In contrast to another cross-sectional cohort study by Lee et al which found a reduction in the foveal vessel density, perfusion density, mean GC-IPL thickness, CFT and RNFL and an increase in the FAZ at the level of the SVP in the hypertensive group compared to controls, our paper did not find any significant differences between the 2 groups at the level of the SVP.…”
Section: Discussionsupporting
confidence: 90%
“…A subsequent cross-sectional study from Korea found that patients with hypertension (n = 140) had significant retinal thinning in nearly all regions assessed as compared with those without hypertension (n = 687). 98 Notably, the hypertensive group was older with a higher prevalence of CVD risk factors. More recently, a single-center study from Italy of 100 patients with hypertension found consistent retinal and choroidal thinning in hypertensive patients with coexistent CKD (defined as an eGFR <60 ml/min per 1.73 m 2 and/or moderate albuminuria) as compared with hypertensive patients with preserved renal function.…”
Section: Retinal Imaging the Kidney And Cvdmentioning
confidence: 99%
“…Dizygotic (DZ) twins were pooled with siblings because the genetic sharing within DZ twin pairs is similar to the genetic sharing between siblings, and the number of DZ twin pairs was too small to be separated 19 . While estimating ICCs, age, sex, axial length, presence of diabetes, and hypertension, and smoking history were adjusted as they may influence macular thickness [33][34][35][36][37] .…”
Section: Statistical Analysesmentioning
confidence: 99%